SOCIO-ECONOMIC CONDITIONS OF MINING LABOUR IN PRAKASAM DISTRICT --- AN EMPIRICAL PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
The mining industry is an important socioeconomic sector that significantly increases India's GDP. Even though the mining industry only makes up 2.2% to 2.5% of the GDP, it accounts for 10% to 11% of the GDP of the whole industrial sector. The study aim is to analyze the economic problems faced by the mining labour and to examine the health status of the mining labour in the study area. The present research study involves both primary and secondary data. Primary data was collected through interview schedule method with the help of a structured questionnaire. The questionnaire consists of definite, concrete and pre- ordered questions. The Likert scaling technique was applied in the questionnaire. For the collection of the research sample , the sampling area selected for the study was Prakasam district in the state of Andhra Pradesh. Purposive and Stratified Random Sampling method was applied for identifying and selecting the requisite sample respondents for the research study. For the identification of sampling units in the selected Prakasam district of Andhra Pradesh, the entire district was demarcated into four mining regions where mining activities were concentrated on a major scale.